Analisis Pemanfaatan Aplikasi OBS Studio Pada Pembelajaran Bahasa Arab Berbasis Hybrid Learning - azhari, Jalaludin Faruk; Asyhari (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2024)
The term "hybrid learning" in the context of education describes a fusion of traditional and online learning approaches. To support hybrid learning, IAIN Madura uses the OBS Studio application. The purpose of the study is to offer a different approach to the time, location, and distance issues that lecturers deal with, which hinder the learning process. Additionally, pupils' ideas and ways of thinking are constrained when traditional teaching approaches are used. Children are consequently unmotivated to study both individually and in groups. This study employs phenomenological inquiry as a qualitative research methodology. The following succinctly describes the results of IAIN Madura's hybrid learning-based Arabic instruction utilizing the OBS Studio application: First, instructors and students feel more relaxed and younger when OBS Studio is used in the hybrid-based learning approach. Second, students' perceptions that studying Arabic may be integrated with information, communication, and technology (ICT) may be strengthened by hybrid learning-based Arabic language instruction utilizing OBS Studio. Third, OBS Studio is a very useful tool for learning Arabic and is a great learning tool. Fourth, OBS Studio can be used as an alternative learning tool that helps with distance learning. Keywords: OBS Studio, Hybrid learning, Arabic Language